Competitive opportunities of the insurance market of the Republic of Kazakhstan in the conditions of integration - Serikova, G.S.; Kudaybergenova, S.K. (BUKETOV BUSINESS REVIEW, 2018)
In modern conditions development of the insurance sector of economy of Kazakhstan is connected with integration processes. The insurance market can’t develop beyond the laws of integration policy of membercountries of the Eurasian Economic Union. The main objective of integration is creation of the effective and competitive uniform insurance market of the EEU capable to react to various financial challenges and threats. The competitiveness of the insurance market provides its financial and investment potential. Potential for development of insurance branch, certainly, is defined by its macroeconomic and microeconomic conditions. In this regard the analysis of competitive opportunities of the Kazakhstan insurance market in the conditions of integration is relevant. In the scientific article on the basis of research of practical aspects the analysis of the level of development of the Kazakhstan insurance market is carried out, current trends of its development are revealed. Results from the analysis show that ensuring competitiveness of the domestic insurance market requires acceptance of a number of effective measures. Further development of the insurance market will depend in many respects on support of the state of integration processes of insurers, the organization of effective management of risks, the effective scheme of reinsurance policy, improvement of business processes of insurance companies, active introduction of new insurance services and products.